Health Expenditures and Economic Growth in Zimbabwe - Manenge, Robson (International Journal of Economics and Financial Issues, 2024)
The literature on the relationship between health expenditure and economic growth continues to grow, albeit without much consensus. The study evaluates the relationship between health expenditure and economic growth in Zimbabwe, a country that repeatedly failed to meet the Abuja Declaration commitment of 15% of the national budget during the period 1980-2020, using the novel method of autoregressive distributed lag model. The study established that there is cointegration among health expenditure, economic growth, trade openness, economic crisis, and fiscal position. The main result is that health expenditure influence economic growth and vice versa. The results show that economic growth is determined by health expenditure, fiscal position, life expectancy, and economic crisis. On the other hand, health expenditure is influenced by economic growth, budget position, trade openness, life expectancy at birth, and economic crisis in the country. The results show that there is a bidirectional relationship between health expenditure and economic growth in the long run. In the short run, economic growth, trade openness, economic crisis and fiscal position significantly determine health expenditure. The study recommends that government should strive to increase budgetary allocations to health in line with the Abuja Declaration while also putting in place pro-growth policies.